1995
DOI: 10.1074/jbc.270.5.2133
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with TrkA Immobilizes gp75 in the High Affinity Nerve Growth Factor Receptor Complex

Abstract: It has been proposed that the high affinity nerve growth factor (NGF) receptor required for NGF response is a complex of two receptor proteins, gp75 and the tyrosine kinase TrkA, but direct biochemical or biophysical evidence has been lacking. We have previously shown using fluorescence recovery after photobleaching that gp75 is highly mobile on NGF-nonresponsive cells, but relatively immobile on NGF-responsive cells. In this report, we show that a physical interaction with TrkA causes gp75 immobilization. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
4

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 42 publications
8
52
4
Order By: Relevance
“…The mechanism by which p75 controls TrkA function probably does not involve TrkA-p75 heterodimers, because they are not likely to be induced by binding of the mAb-based ligands; however, the possibility that receptor heterodimers preexist on the cell membrane and are not ligand dependent cannot be ruled out (Wolf et al, 1995;Ross et al, 1996). Furthermore, it is also possible that a positive modulation of bound p75 on TrkA occurs (Verdi et al, 1994;Canossa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which p75 controls TrkA function probably does not involve TrkA-p75 heterodimers, because they are not likely to be induced by binding of the mAb-based ligands; however, the possibility that receptor heterodimers preexist on the cell membrane and are not ligand dependent cannot be ruled out (Wolf et al, 1995;Ross et al, 1996). Furthermore, it is also possible that a positive modulation of bound p75 on TrkA occurs (Verdi et al, 1994;Canossa et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant neurotrophins that bind Trk receptors preferentially over p75 function like wild-type neurotrophins in biological assays (Ibáñez et al, 1992;Barker and Shooter, 1994;Ryden et al, 1995); however, NGF seems to dock onto multiple sites of TrkA, [the IgG-like domain (Perez et al, 1995) and/or the leucine zipper domain (Windisch et al, 1995)]. Ligand binding to multiple TrkA sites may cause signaling and may lead to p75 immobilization and p75-independent signals (Wolf et al, 1995;Ross et al, 1996). This would be consistent with the agonistic effect of anti-TrkA polyclonal antisera, which has multiple binding sites (Clary et al, 1994).…”
Section: ϫ10mentioning
confidence: 99%
“…Newly synthesized protein accumulates in the cytoplasm during G1 phase. In S phase it is located mostly in the nucleus and, following the initial step of DNA synthesis, p53 is again found in the cytoplasm (Sathanam et al, 1991;Wolf et al, 1995). Recently it has been shown that in PC12 cells transfected with the val 135 ts p53 mutant, it localizes in the cytoplasm, suggesting an epigenetic e ect of p53 (Knippschild et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that high a nity binding may require expression of both components (Hantzopoulos et al, 1994;Hempstead et al, 1991;Wolf et al, 1995). NGF binding to trk induces dimerization or oligomerization of receptor molecules, as well as tyrosine transphosphorylation and activation of intrinsic receptor tyrosine kinase (Kaplan et al, 1991b;Kaplan and Stephens, 1994).…”
mentioning
confidence: 99%
“…Although the molecular nature of this association is not clear, it is interesting to note that the C terminus of p75 N TR contains the critical residues mediating the interaction of various ion channels with the postsynaptic density protein PSD95 (Kornau et al, 1995). Finally, p75 N TR molecules carrying a 55 amino acid deletion in the intracellular domain are profoundly affected in cellular sorting, ligand internalization, signaling capacities, and lateral mobility in the membrane (Le Bivic et al, 1991;Dobrowsky et al, 1995;Wolf et al, 1995). The same mutants also have altered binding properties (Hempstead et al, 1990), indicating a role of the intracellular domain in the determination of ligand affinity.…”
Section: P75 Ntr On Neurons and Transformed Cellsmentioning
confidence: 99%